Changes in soil bacterial community characteristics in patches of different vegetation types under different stages of restoration in the desert of northern China - Haonian Li; Yumei Liang; Zhongju Meng; Xiaomen Ren; Ruibing Meng; Feiyan Zhao (Ecology and Evolution)
Abstract In desert areas, the process of mobile sandy land changing to semi‐fixed sandy land and eventually to fixed sandy land after undergoing vegetation restoration is inevitable. The presence of shrub patches and herb patches is common in this restoration process. No relevant studies have reported the soil bacterial community characteristics of different vegetation‐type patches (shrub patches and herb patches) under different stages of restoration. Therefore, we utilized long‐established experimental plots to collect soil from 0–20 cm soil layer under shrub patches (dominated by Salix psammophila) and herb patches under different stages of restoration (i.e., mobile sand land, semi‐fixed sand land, and fixed sand land), by determining soil physicochemical properties, enzyme activities, and soil bacterial communities. Our results found that soil bacterial α‐diversity under different restoration stages showed higher shrub patches than herb patches. The dominant bacterial communities (phyla) in shrub patches and herb patches at different recovery stages were Actinobacteria, Proteobacteria, and Bacteroidota. When the mobile sandy land returned to fixed sandy land, the relative abundance of Actinobacteria and Bacteroidota gradually decreased under shrub patches and herb patches, while the relative abundance of Proteobacteria increased significantly. In addition, herb patches significantly increased the relative abundance of bacteria (genus) relative to shrub patches at different stages of recovery. Soil nutrients, soil fine particles, and soil enzyme activities were significantly higher under shrub patches than under herb patches when fixed sandy land due to differences in life form and architecture between shrub patches and herb patches. Based on this, soil bacterial community composition and diversity under shrub patches were driven by more soil properties during the restoration of sandy land. This study complements the dynamic recovery processes and driving mechanisms of soil bacterial community structure under different vegetation patches in sandy areas, especially in the context of global climate change.